2011
DOI: 10.1007/s00464-011-1754-6
|View full text |Cite
|
Sign up to set email alerts
|

Image inversion and digital mirror-image technology aid laparoscopic surgery task performance in the paradoxical view: a randomized controlled trial

Abstract: This is the first study to demonstrate that when in the paradoxical viewpoint, altering the image on the video monitor, either by digitally flipping or inverting the image, can improve surgical task performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Several studies have been conducted on the view for laparoscopic surgery. [8][9][10][11][12][13] All these studies demonstrated a limitation of the laparoscopic performance of the assistant in the conventional view, and mental rotation, digital mirror-image technology, or monitor rotation is suggested as an alternative. In the study by Gill et al, 12 surgical task performance improved by digitally f lipping or inverting the laparoscopic view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted on the view for laparoscopic surgery. [8][9][10][11][12][13] All these studies demonstrated a limitation of the laparoscopic performance of the assistant in the conventional view, and mental rotation, digital mirror-image technology, or monitor rotation is suggested as an alternative. In the study by Gill et al, 12 surgical task performance improved by digitally f lipping or inverting the laparoscopic view.…”
Section: Discussionmentioning
confidence: 99%
“… 8 - 13 All these studies demonstrated a limitation of the laparoscopic performance of the assistant in the conventional view, and mental rotation, digital mirror-image technology, or monitor rotation is suggested as an alternative. In the study by Gill et al, 12 surgical task performance improved by digitally flipping or inverting the laparoscopic view. However, we report a difference in that hand-eye discordance was eliminated by changing both the top and bottom and left and right, by rotating the laparoscopic view not just up and down or left and right.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of other methods such as VR trainers with the BTs showed that differences were present in some of the measured outcomes. Nevertheless, these results were based on small randomized controlled trials and no specific conclusions could be drawn in the case of novice trainees .…”
Section: Hands‐on Training In Laparoscopy‐box Trainersmentioning
confidence: 99%
“…Several studies have suggested that rotating the view on the monitor for the assistant by 180 degrees (left-right reversed and upside-down image) with the image converter improves task performance with mirror images 912 . However, most facilities do not have an image converter, which is an expensive piece of equipment.…”
Section: Introductionmentioning
confidence: 99%